Monetary Policy and Leading Indicators of Inflation in Sweden - Baumgartner, Josef (IMF Working Papers; Working Paper ;, 1997)
This paper derives a set of leading indicators of inflation for Sweden. It also discusses methodological and policy issues pertaining to the estimation of these indicators. The main findings are: (1) narrow money is the most powerful leading inflation indicator; (2) broad money and inflation expectations have significant predictive information on inflation; (3) the output gap, interest rates, and the credit aggregate have some predictive information on inflation, and this information is confined to a shorter time horizon than either the monetary aggregates or inflation expectations; and (4) implied forward rates have only weak predictive information on inflation.